2003
DOI: 10.1068/a3542
|View full text |Cite
|
Sign up to set email alerts
|

The Life Course and Residential Mobility in British Housing Markets

Abstract: There is a substantial research literature on residential mobility in general, and the role of housing space in triggering moves in particular. The authors extend that research to mobility in British housing markets, using data from the British Household Panel Survey. They confirm the applicability of the general residential mobility model and also confirm the value both of pooled cross-sectional and of true longitudinal models of residential change. Age, tenure, and room stress (housing-space requirements) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
231
0
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 280 publications
(254 citation statements)
references
References 21 publications
8
231
0
15
Order By: Relevance
“…The evidence concerning the association between the occurrence of childbirth and migration is mixed. In some studies, no effect (Clark and Huang 2003;Clark and Ledwith 2006) or even a negative effect (Li 2004) was found. Clark and Huang (2003) found childbirth to have an impact on moving in a longitudinal analysis but not in a cross-sectional analysis.…”
Section: Migration In Early Adulthoodmentioning
confidence: 99%
See 4 more Smart Citations
“…The evidence concerning the association between the occurrence of childbirth and migration is mixed. In some studies, no effect (Clark and Huang 2003;Clark and Ledwith 2006) or even a negative effect (Li 2004) was found. Clark and Huang (2003) found childbirth to have an impact on moving in a longitudinal analysis but not in a cross-sectional analysis.…”
Section: Migration In Early Adulthoodmentioning
confidence: 99%
“…In some studies, no effect (Clark and Huang 2003;Clark and Ledwith 2006) or even a negative effect (Li 2004) was found. Clark and Huang (2003) found childbirth to have an impact on moving in a longitudinal analysis but not in a cross-sectional analysis. Michielin and Mulder (2008) found that short-distance moves were frequent during pregnancy.…”
Section: Migration In Early Adulthoodmentioning
confidence: 99%
See 3 more Smart Citations